Minoxidil and Dexamethasone Eluting Nanofiber Dressing for Cutaneous Wound Healing in Rat - Saber khozan; Behsa Salehian; Fatemeh Montaghimi; Yaeghob Sharifi; Anahita Fathi-Azarbayjani (Tabriz University of Medical Sciences, 2023)
Background: Minoxidil is an antihypertensive agent and vasodilator which may help to promote local blood flow thus hastening the closure of excisional skin wounds. Corticosteroids may down-regulate wound healing. This work aims to develop and characterize nanofiber-eluting dexamethasone and minoxidil and investigate their effect on wound healing in a rat model. Methods: Minoxidil and dexamethasone-loaded wound dressings were developed and characterized with scanning electron microscopy (SEM) and Fourier transform infrared spectroscopy (FT-IR). In vitro, drug release studies were performed for 12 days. To model the wound-healing activity of the developed formulations, excisional wounds were created on the dorsal section of male rats. Results: All the electrospun wound dressing nanofibers displayed smooth structures and surfaces without drug crystals. Histological results of Hematoxylin & Eosin and Masson's trichrome staining indicate wound healing suppression in the dexamethasone-treated group and good healing activity in the minoxidil-treated group. Here we identified that the application of topical minoxidil can be effective for wound healing probably driven by the anagen hair growth while dexamethasone suppresses collagen production and prevents scar formation. Conclusion: The findings suggest that this minoxidil and dexamethasone wound dressing can potentially be developed as a new treatment modality in the clinic to accelerate wound healing while preventing scar formation.